Physico-Mechanical Properties of Two Native Tree Species in the Philippines and Their Potential as Alternatives to Exotic Industrial Tree Plantation Species - Oliver S. Marasigan; Shereyl A. Daguinod; Jayric F. Villareal (Environment and Natural Resources Journal)
The potential of Bagalunga (Melia azedarach L.) and Kalumpit (Terminalia microcarpa Decne) as alternatives to Falcata [Falcataria falcata (L.) Greuter & R. Rankin], Gmelina (Gmelina arborea Roxb. ex Sm.), and Mahogany (Swietenia macrophylla King) were evaluated by assessing their physico-mechanical properties in accordance with ASTM D143-52: 2019 standards. Results showed that Mahogany had the lowest green moisture content (MC) at 90.60% and the highest basic relative density (RDb) at 0.52, while Falcata exhibited the highest green MC (193.98%) and the lowest RDb (0.29). Bagalunga displayed the highest shrinkage values [tangential shrinkage (TS): 6.63%, radial shrinkage (RS): 4.48%, volumetric shrinkage (VS): 10.81%], whereas Mahogany showed the lowest shrinkage (TS: 3.59%, RS: 3.11%, VS: 6.81%) but the highest longitudinal shrinkage (LS) (0.42%). Mahogany recorded the highest modulus of rupture (MOR) (63.65 MPa and 66.96 MPa at green and 12% MC, respectively), and excelled in compression [parallel (27.28 MPa and 35.62 MPa), perpendicular (7.14 MPa and 7.89 MPa)], hardness [side (4.67 kN and 4.20 kN), end (5.48 kN and 5.49 kN)], and shear strength (8.37 MPa and 10.37 MPa). Kalumpit exhibited the highest toughness in both green and 12% MC conditions (48.51 J/Spec and 42.62 J/Spec), along with the highest SPL (33.42 MPa) and MOE (8.58 GPa) at 12% MC. Gmelina had the highest MOE (7.12 GPa), while Mahogany showed the highest SPL (25.50 MPa) in the green condition. Height levels significantly affected TS and VS, while mechanical properties showed minimal variation. Farmers may consider Bagalunga and Kalumpit as alternative species. The application of silvicultural practices is essential for improving growth, optimizing rotation cycles, and ensuring sustainability for native tree species.